Peran Aset Nonfisik dalam Meningkatkan Kinerja Organisasional pada UKM Sektor Manufaktur di Kota Palu - Moelyono, Mauled (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
The aim of this research is toanalyze the role of intangible asset in improving organizational performance of Small Medium Enterprises (SMEs) in manufacture sector in Palu. This research was designed as explanatory research. The sample was determined using stratified proportional random sampling and consists of 175 units of SMEs. The data collected by questionnaire to the directors of the SMEs were analyzed using Structural Equation Modeling (SEM). This research has successfully proved the role of intangible asset in improving organizational performance through the role of social capital; it is by moderating the influence of business networking and organizational learning to the organizational performance of SME's.